Pengaruh Struktur Modal dan Profitabilitas Terhadap Harga Saham Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Michael Bungaran Sitanggang; Eli Safrida; Khanti Listya; Abdul Rahman (Jurnal Minfo Polgan, 2026)
This study aims to examine the effect of capital structure and profitability on stock prices, with firm size as a moderating variable, in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The background of this research is based on the inconsistency of previous study results regarding the influence of capital structure and profitability on stock prices, as well as the limited research on the moderating role of firm size, particularly in the energy sector. The theory used in this study is the Signaling Theory, which explains that capital structure and profitability can provide either positive or negative signals to investors, ultimately affecting the company's stock price. The sampling method employed in this research is purposive sampling, resulting in 82 samples drawn from 47 companies that constitute the research population. The method used in this study is multiple linear regression and Moderated Regression Analysis (MRA), with the assistance of SPSS version 29 for testing. The findings indicate that capital structure has a significant effect on stock prices, while profitability does not show a significant influence. Regarding the moderating role, firm size is proven to weaken the relationship between capital structure and stock prices but does not moderate the relationship between profitability and stock prices.